2019
DOI: 10.1136/neurintsurg-2019-015389
|View full text |Cite
|
Sign up to set email alerts
|

4D-CT angiography versus 3D-rotational angiography as the imaging modality for computational fluid dynamics of cerebral aneurysms

Abstract: Background and purposeComputational fluid dynamics (CFD) can provide valuable information regarding intracranial hemodynamics. Patient-specific models can be segmented from various imaging modalities, which may influence the geometric output and thus hemodynamic results. This study aims to compare CFD results from aneurysm models segmented from three-dimensional rotational angiography (3D-RA) versus novel four-dimensional CT angiography (4D-CTA).MethodsFourteen patients with 16 cerebral aneurysms underwent nov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 29 publications
(43 reference statements)
0
8
0
Order By: Relevance
“…Four-dimensional CT (4D-CT) adds a time axis to three-dimensional data and allows continuous CT imaging on a timeseries basis. This method has widespread clinical application for assessments such as evaluation of blood ow dynamics [16][17][18][19]. In the eld of orthopedic surgery, this method is expected to improve evaluations of joint dynamics and functions [20].…”
Section: Introductionmentioning
confidence: 99%
“…Four-dimensional CT (4D-CT) adds a time axis to three-dimensional data and allows continuous CT imaging on a timeseries basis. This method has widespread clinical application for assessments such as evaluation of blood ow dynamics [16][17][18][19]. In the eld of orthopedic surgery, this method is expected to improve evaluations of joint dynamics and functions [20].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the differences in imaging principle and scanning conditions, different imaging modalities with unique features will show different depictions of aneurysmal structures 5 17–20. In this study, the morphological comparison showed geometric consistency between both imaging techniques for aneurysm complexes.…”
Section: Discussionmentioning
confidence: 60%
“…A possible explanation is due to the non-ICA subgroup with greater differences in TAWSS and smaller differences in PAWSS, but the differences were not statistically significant for TAWSS and PAWSS. Cancelliere et al 20 postulated that hemodynamic results may be affected by flow rates estimated according to the inlet diameter of parent arteries, which varies among different image techniques. Despite showing no statistical difference between 3DRA and silent MRA in average parent vessel diameter (p=0.7615), model comparisons revealed differences in parent vessel models, especially for the distal aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to classical CTA, with a longer acquisition time or several acquisitions over a given period, 4D-CTA records the influx and efflux of the contrast product and morphological changes of IA within a cardiac cycle when the acquisition is ECG-gated ( 64 ). 4D-CTA is mostly used in the evaluation of hemorrhagic/ischemic stroke and vascular malformations and has been proposed to replace the gold standard 3D-DSA for follow-up imaging since it produces accurate IA geometrics and reliable CFD results when compared to 3DRA ( 65 ).…”
Section: Hemodynamic Imagingmentioning
confidence: 99%